2014
DOI: 10.1310/sci2004-277
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Analysis of the Potential Association Between SCI Secondary Health Conditions and Daily Activities

Abstract: Maximizing participation in DAs requires minimizing SHCs in every instance. Understanding the association between SHCs and DAs may facilitate targeted care resulting in less severe SHCs, greater participation in DAs, and benefits to both the individual and society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…In contrast to our study, they included many more items: 21 SHCs and 26 Daily Activities. 12 Qualitative data analysis, a pilot study of Callaway et al, focused on the SHCs spasm, pain, sexual dysfunction, pressure sores, fatigue and the impact of SHCs on life role participation. They described an overall negative impact that these items can have on daily life.…”
Section: Impact On Functioning At Home and Social Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to our study, they included many more items: 21 SHCs and 26 Daily Activities. 12 Qualitative data analysis, a pilot study of Callaway et al, focused on the SHCs spasm, pain, sexual dysfunction, pressure sores, fatigue and the impact of SHCs on life role participation. They described an overall negative impact that these items can have on daily life.…”
Section: Impact On Functioning At Home and Social Activitiesmentioning
confidence: 99%
“…Kennedy et al 11 reported a significant impact of SHCs on independence and activities in a multicenter, cross-sectional study of SCI patients 3-18 months after discharge from three rehabilitation centers. Participants in the study by Cobb et al 12 reported that because of SHCs their participation in 26 daily activities was restricted. Overall injury-related variables influence life satisfaction through functional health status, especially social functioning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has highlighted the effect of secondary health conditions on community participation and long-term adjustment of persons with tSCI. 70–73 Therefore, having additional indicators to monitor secondary health conditions and the clinical practice on preventing/treating these conditions will provide a measure of the underlying cause hampering meaningful participation and will identify opportunities to improve practice. Development of these indicators will align with the recommendations from the recent SCI Summits on secondary health conditions (pressure ulcers, neuropathic pain, and urinary tract infections/urological health); a common goal of these summits is to develop and implement evidence-based practice guidelines regionally and nationally.…”
Section: Overview Of Application Of the Evidence-based Policy-making mentioning
confidence: 99%
“…This leads not only to motor paralysis and sensory changes but also to various autonomic dysfunctions, including bowel, bladder and sexual dysfunction, abnormal blood pressure and heart rate control and sweating and temperature dysregulation. 1,2 These autonomic dysfunctions result in a significant burden to persons with SCI, their family members and the health-care system in terms of reduced participation in activities of daily life, 3 barriers to employment 4 and lower quality of life. 5 In a recent survey by Anderson, 6 persons with SCI ranked regaining bladder and bowel function as a high priority, surpassing regaining the ability to walk.…”
Section: Introductionmentioning
confidence: 99%